(untitled) (Mustansiria Dental Journal, 2018)
The aim was to assess the vertical and horizontal dimensional changes in the maxillary and mandibular dental arches after the unilateral premature loss of deciduous molars. Methods: The sample consist of 100 child between 8-9 years of age with unilateral loss of first or second deciduous molars, either in the maxillary or mandibular arches, Study casts were made and measurements conducted on the Auto sketch program on the computer , The data obtained was subjected to statistical analysis. The Results of the study showed that when comparing the mean values of the loss groups with the control group a statistically significant difference in the maxillary (A) distance after the premature loss of first or second deciduous molars, however a high significant difference statistically in the (ML) distance recorded after the premature loss of maxillary second deciduous molar ,while in the mandibular arch a statistically high significant difference observed in most of the vertical and horizontal distances following premature loss of second deciduous molar. Conclusions: The major effect on the dental arch length and width following the premature loss of the deciduous molars, indicating the need for fitting the space maintainers’ appliances as soon as the extraction is the final decision to the dentist.